Epiphyseal Fracture of the Coracoid Process Occurring at the Conjoined Tendon Origin - Kenjiro Nakama; Masafumi Gotoh; Yasuhiro Mitsui; Takahiro Okawa; Fujio Higuchi; Kensei Nagata (Case Reports in Orthopedics)
Fracture of the coracoid process is uncommon, and most previous studies have reported this fracture occurring in association with direct trauma to the shoulder or transmission of force from the upper arm or elbow (Ada and Miller 1991, Benton and Nelson 1971, Eyres et al. 1995). We present a case in which epiphyseal fracture occurred at the origin of the conjoined tendon following excessive muscle contraction. We believe this represents the first description of such a method of injury.